No signs of meristem senescence in old Scots pine. (12th February 2014) - Mencuccini, Maurizio; Oñate, Marta; Peñuelas, Josep; Rico, Laura; Munné‐Bosch, Sergi; Salguero‐Gómez, Roberto
Summary Ageing and senescence in plants remain poorly understood. Although meristem totipotency may allow woody perennials to be immortal, relative growth and photosynthetic rates typically decline with age. Trees of ages between 129 and 534 years were selected in one of the oldest extant populations of Scots pine. Apical branches were propagated by grafting onto homogeneous juvenile rootstock to eliminate the effects of size and environmental variability and isolate those due to age. The hormonal profile of leaves and seeds along with markers of the physiological status of leaves and their pattern of DNA cytosine methylation were measured 15 years after grafting. The percentage of total methylated loci in nuclear DNA increased with increasing meristematic age. However, only very few significant relationships were found between levels of phyto‐hormones, pigments or physiological markers either in leaves or seeds and age of the meristem. In addition, shoots grafted from old trees grew as fast as those from younger trees and produced the same number of germinable seeds. Synthesis. We conclude that changes in DNA methylation can occur in old trees. The lack of apparent physiological deterioration in the grafted plants suggests that meristem senescence is not the main factor triggering whole‐plant ageing in Scots pine.